2021
DOI: 10.1155/2021/2107623
|View full text |Cite
|
Sign up to set email alerts
|

Connection-Based Multiplicative Zagreb Indices of Dendrimer Nanostars

Abstract: The field of graph theory is broadly growing and playing a remarkable role in cheminformatics, mainly in chemistry and mathematics in developing different chemical structures and their physicochemical properties. Mathematical chemistry provides a platform to study these physicochemical properties with the help of topological indices (TIs). A topological index (TI) is a function that connects a numeric number to each molecular graph. Zagreb indices (ZIs) are the most studied TIs. In this paper, we establish gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…To study the paraffin boiling point, Harry Wiener [24] developed the first distance-based topological index. There are numerous different forms of topological indices, such as, vertex-degree based indices [25][26][27][28][29][30][31][32][33][34][35], distance-based indices [15,[36][37][38][39], and connection based indices [20,[40][41][42][43]. Among the numerous types of molecular descriptors, vertex-degree based molecular descriptors are commonly used [25-30, 44, 45], however, the connection based topological indices attracted significant attention of the researchers more recently due to their high predictive ability [20,43,46].…”
Section: Introductionmentioning
confidence: 99%
“…To study the paraffin boiling point, Harry Wiener [24] developed the first distance-based topological index. There are numerous different forms of topological indices, such as, vertex-degree based indices [25][26][27][28][29][30][31][32][33][34][35], distance-based indices [15,[36][37][38][39], and connection based indices [20,[40][41][42][43]. Among the numerous types of molecular descriptors, vertex-degree based molecular descriptors are commonly used [25-30, 44, 45], however, the connection based topological indices attracted significant attention of the researchers more recently due to their high predictive ability [20,43,46].…”
Section: Introductionmentioning
confidence: 99%
“…Further, Liu et al [25] found the topological properties of neural networks. Recently, Sattar et al [26][27][28] worked on computing the general expression of ZIs for two types of dendrimers. For the other terminologies not discussed in this paper, the readers are referred to [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Du et al [21] utilized connection-based modified FZI to find the extremal alkanes. Recently, Sattar et al [22] computed the general expressions to compute MZCI of dendrimer nanostars. Furthermore, in 2020, Ali et al [23] worked out to calculate the modified ZCIs for T-sum graphs.…”
Section: Introductionmentioning
confidence: 99%